Downscaling GRACE Predictions of the Crustal Response to the Present‐Day Mass Changes in Greenland. Issue 5 (22nd May 2019) - Wang, Linsong; Khan, Shfaqat A.; Bevis, Michael; van den Broeke, Michiel R.; Kaban, Mikhail K.; Thomas, Maik; Chen, Chao
Abstract: The GRACE mission has had a revolutionary impact on the study of Earth system processes, but it provides a band‐limited representation of mass changes. This is particularly problematic when studying mass changes that tend to be concentrated in fairly narrow zones near the edges of the Greenland Ice Sheet. In this study, coarse‐resolution estimates of the mass change derived from GRACE have been enhanced by the introduction of heuristic scaling factors applied to model surface mass balance and observed surface elevation change. Corresponding results indicate large spatial heterogeneity in the gridded scaling factors at the 0.5° × 0.5° scale, reflecting significant mass losses concentrated along the ice sheet margin and relatively small internal ice sheet changes at higher elevations. The scaled GRACE‐derived vertical displacements are in the range from −2 to 14 mm/year from 2003 to 2015. The Greenland GPS network was used to examine the downscaling GRACE predictions of the crustal displacements. The results show consistency of scaled GRACE‐predicted and GPS‐observed seasonal and long‐term uplift in major drainage basins of Greenland. Our results indicate that GRACE predictions underestimate vertical displacements at sites located in regions characterized by concentrated loads, but perform well in other regions. Differences between predicted and observed uplift rates are mainly caused by the sensitivity kernels, because GPS and GRACE estimates are based on weighted averages of mass loss in different sensitivity ranges. Moreover, a large uncertainty in the glacial isostatic adjustment correction may also cause errors in the GPS‐to‐GRACE ratio. Key Points: GRACE results can be improved by using scaling factors estimated from two models of surface mass fields in Greenland Scaled GRACE‐derived and GPS‐observed vertical displacements were compared at 53 Greenland GPS Network (GNET) stations GRACE‐based estimates of accurate uplift rates in Greenland needs to consider the spatial pattern of ice loss and reliable GIA correction